Plant Morphology and Fruit Quality Traits Affecting Yield and Post-Harvest Behavior of Two Highbush Blueberry Cultivars in Central Chile - Sebastián Romero-Bravo; Miguel Araya-Alman; Claudia Moggia; Gustavo A. Lobos; Felipe Calderon; Sergio Espinoza (Horticulturae)
In this study, we address the question of the most important factors influencing yield and fruit quality in highbush blueberries. An experiment was carried out to investigate the relationship between yield components and (i) plant yield, (ii) fruit quality traits, and (iii) fruit firmness post-harvest in two Vaccinium corymbosum L. blueberry cultivars (‘Duke’ and ‘Brigitta’). In a field in central Chile (35°15′39″ S; 71°14′32″ W) during the growing season 2018–2019, we measured the number of canes (NC), length of the first shoot (LFS), age of the first shoot (AFS), diameter of the first shoot (DFS), flower buds per cane (FBC), number of one-year shoots per cane (SPC), flowers per bud (FPB), fruit set percentage (FSP), yield (YLD), fruit weight (FW), fruit firmness at harvest (FF), fruit diameter at harvest (FD), soluble solids/acid ratio at harvest (SS:AC), and fruit firmness after harvest (FFpos). The most important factors affecting yield and fruit quality were FBC, SPC, and FF. Our results suggest that FBC and SPC could be managed agronomically to optimize fruit load and light interception.